Language Diversity and New Media: Issues of Multimodality and Performance - Gadanidis, George; Borba, Marcelo [UNESP]; Scucuglia, Ricardo [UNESP] (Springer Nature, 2016)
Language diversity in mathematics education is generally concerned with “multiple language use, learning through second or additional languages, learning through minority or oppressed languages, or through majority or dominant languages” (ICMI Study 21 Discussion document—see Appendix). For example, one issue in language diversity is the hegemonic role played by English in many countries to displace mother tongue education (Kirkpatrick, 2007; Phillipson, 2009). In this chapter, we take up the suggestion made by Marilyn Martin-Jones during the plenary of the ICMI Study 21 conference that future issues on language diversity need to be concerned with the use of digital media, and we explore the relationship between language diversity and new media.
Keywords: Language Diversity; Mathematical Idea; Mathematics Classroom; Visceral Sensation; Wide Audience